PEMBUATAN DASHBOARD REGISTRASI SISWA BARU SEKOLAH SMA YPPK ASISI SENTANI MENGGUNAKAN METODE USER CENTERED DESIGN - Renly X.P Karubun; Prihadi Beny Waluyo; Kristian Adi Nugraha (Fakultas Teknologi Informasi, 2022)
Yppk Assisi Sentani High School is one of the senior high schools located in Sentani City, Jayapura Regency. The registration system used for prospective newstudents is still manual until now. Where when registering, prospective new students are still required to come to the school directly. On the other hand, Jayapura district already has an internet connection that is quite good for accessing websites, especially in the city of Sentani, where Yppk Assisi Sentani High School is located. Based on the problems encountered, I as the author tried to help the process of accepting new students by creating a registration dashboard interface for SMA Yppk Assisi Sentani using the User Centered Design (UCD) method. In addition, testing will be carried out using the Usability Testing and System Usability Scale (SUS) methods. The satisfaction test that has been carried out on users using SUS shows an average percentage of 80 for admins andteachers while for students the average obtained is 73. Therefore, it can be concluded that the registration dashboard of Yppk Assisi Sentani High School is well received. The registration dashboard interface for SMA Yppk Assisi Sentani is expected to be useful for prospective students who will register, because newprospective students can register from anywhere without having to come to school so that it will save time and be more efficient.